HUBUNGAN INTERNAL LOCUS OF CONTROL DENGAN FEAR OF SUCCESS PADA POLISI WANITA YANG SUDAH MENIKAH DI MAPOLDA JAWA TENGAH - Marita Riantika; Alice Zellawati; Brigitan Argasiam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
This research aims to determine the relationship between internal locus of control and Fear of Success among married female police officers in MAPOLDA Central Java. The population in this study were all female police officers who were married and served at the Central Java Regional Police Headquarters, totaling 115 people with a sample of 78 married female police officers at the Central Java Regional Police Headquarters. The sampling technique uses incidental sampling technique. This research uses a psychological scale data collection method in the form of a Likert scale which consists of two scales, namely, the internal locus of control scale with 28 items (? = 0.900) and the Fear of Success scale with 24 items (? = 0.899). Based on the hypothesis proposed in this research, namely: